2014
DOI: 10.1016/j.ijid.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Chagas disease (Trypanosoma cruzi) and HIV co-infection in Colombia

Abstract: Background: Recently new aspects of the immunopathology of Chagas disease have been described in patients infected with HIV and unusual clinical manifestations such as cutaneous lesions, involvement of central nervous system and/or serious cardiac lesions related to the reactivation of the parasite have been reported. Two uncloned Trypanosoma cruzi strains previously isolated from chronic chagasic patients with HIV co-infection were studied in order to evaluate the impact of the immunosuppression on the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 4 publications
2
15
0
Order By: Relevance
“…Unlike that generally occurs in Brazil, TcI is the main agent of chronic Chagas disease in some American countries (e.g., Venezuela and Colombia), where the patients can develop severe and fatal cardiomyopathy (usually without digestive megasyndromes), as well as meningoencephalitis in immunocompromised individuals [6][7][8][43][44][45][46][47][48][49][50] . Such discrepancy deserves further investigations, but many factors should be considered for attempting to explain it, as the genetic diversity of both parasites and human beings, and the epidemiological conditions that favor the selection of T. cruzi genotypes by local vectors and hosts [51][52][53] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike that generally occurs in Brazil, TcI is the main agent of chronic Chagas disease in some American countries (e.g., Venezuela and Colombia), where the patients can develop severe and fatal cardiomyopathy (usually without digestive megasyndromes), as well as meningoencephalitis in immunocompromised individuals [6][7][8][43][44][45][46][47][48][49][50] . Such discrepancy deserves further investigations, but many factors should be considered for attempting to explain it, as the genetic diversity of both parasites and human beings, and the epidemiological conditions that favor the selection of T. cruzi genotypes by local vectors and hosts [51][52][53] .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the sequencing analysis of the TcI isolate (CT-IOC 541) showed that it is genetically closer to Sylvio X10, a stock identified as TcId 60 , a sub-group related to sylvatic cycles, which was also found by Câmara et al 38 in Northeastern Brazil. It is worth mentioning that TcId (or TcI sylvatic) was identified in the heart and brain of patients with severe Chagas disease outside Brazil 46,49 . In the present study, the isolate CT-IOC 541 and the Colombian strain showed the same banding pattern at the ME-1 locus, which was distinct from that of the Dm28c stock (Figure 4), a finding that corroborates the variability within TcI.…”
mentioning
confidence: 99%
“…Several studies revealed that different T. cruzi Discrete Typing Units (DTUs) participate in human T. cruzi —HIV coinfection (Perez-Ramirez et al, 1999 ; Lages-Silva et al, 2002 ; Burgos et al, 2005 ; Hernandez et al, 2014 ). Moreover, in a multiclonal infection involving DTUs I and V/VI, we reported that CNS histotropism was ascribed to a DTU I population as the etiological agent of meningoencephalitis (Burgos et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…48 Studies showing the impact of this genetic variability on HIV coinfection are scarce. These studies 49,50 have suggested a differential tissue tropism of the infecting DTUs and have reported mixed infections in coinfected patients, observing TcI and TcII-or TcI, TcV, and TcVI-in the blood, heart, and brain tissue of Chagas disease patients with HIV/AIDS coinfection with cardiomyopathy and encephalopathy. Among immunocompetent patients, Chagas disease can be present as an acute manifestation, but chronic forms are diagnosed more frequently.…”
Section: Chagas Diseasementioning
confidence: 99%